Digital transformation of russian economy: challenging the highest rank in the global innovation development - Lazarev, Gennadiy I.; Varkulevich, Tat’ayna V.; Andreev, Viacheslav A. (Nexo Revista Científica, 2021)
A simple prognostic method was applied to estimate the percentage ratio of the digital economy in Russia’s GDP relying on technology solutions expenditure and sectoral investment. The research indicates a significant impact of Russia’s digital sector on innovation development in B2B, B2G, and B2C segments. The prognostic analysis shows the extension of on-line education, social networking, e-commerce, private and corporate banking, and end-to-end technology solutions in manufacturing. The findings point at the opportunity for the sectoral investment extension and steady annual growth 7-8 % in the next few years. Due to requirements on updating the technological solutions in the related public services, the digital sphere can support the annual growth in the national economy by 1,0-1,2 % until 2024. Respectively the digital economy in Russia will be growing faster the world's average to provide the sector’s contribution of 8,0-8,1 % in GDP by 2024. The findings show the digital platforms are becoming a driver for innovation development integrating the production process, cloud resources, data analysis, and e-learning services. The research contains hints on improving the research efficiency and winning the talent battle that promises to improve the country’s global innovation and economic ranks.